Feasibility of Robotic-Assisted Neurovascular Interventions: Initial Experience in Flow Model and Porcine Model. Issue 2 (17th April 2019) - Britz, Gavin W; Tomas, Johnny; Lumsden, Alan
Abstract: BACKGROUND: Despite advances in robotic-assisted technology for cardiac and peripheral vascular interventions, a robotic-assisted platform for neurovascular intervention is not yet available. OBJECTIVE: To evaluate the feasibility of the CorPath ® GRX robotic-assisted platform (Corindus Inc, Waltham, Massachusetts) for neurovascular interventions through preclinical study. METHODS: The robotic system was tested for its ability to accurately navigate a variety of common neurovascular devices in an in Vitro flow model and in a live, anesthetized pig, under conditions and following procedures appropriate for clinical intervention. An access catheter was introduced manually at the equivalent of the common carotid artery in both models. Endovascular wires and catheters were navigated through the external and internal carotid artery and posterior cerebral vasculature under robotic assistance, using 0.014 in guidewires, 2.4F/1.7F microcatheters, bare-metal stents, and embolic coils. RESULTS: All procedures in both the flow and porcine models, including navigation, wiring, and deployment of the stent and coils, were performed successfully with no technical complications. There was no evidence of extravasation, dissection, thrombosis, or other vascular injury when angiography was compared before and after the live-animal procedure. CONCLUSION: This is the first study to demonstrate that use of a robotic-assisted platform is feasible for intracranial neurovascular intervention. The robotic system was successful at navigating and deploying the small-gauge devices specific to neurovascular procedures. Given the potential benefits of robotic-assisted surgery for the patient and the surgeon, further investigation is warranted for this indication.